A case for interest rate smoothing - Mikael Bask (Bank of Finland, 2007)
The aim of this paper is to determine whether it would be desirable from the perspective of macroeconomic balance for central banks to take account of nominal exchange rate movements when framing monetary policy. The theoretical framework is a small, open DSGE economy that is closed by a Taylor rule for the monetary authority, and a determinate REE that is least-squares learnable is defined as a desirable outcome in the economy. When the policy rule contains contemporaneous data on the output gap and the CPI inflation rate, the monetary authority does not have to consider the exchange rate as long as there is sufficient inertia in policy-making. In fact, due to a parity condition on the international asset market, interest-rate smoothing and a response to changes in the nominal exchange rate are perfectly intersubstitutable in monetary policy. In other words, we give a rationale for the monetary authority to focus on the change in the nominal interest rate rather than its level in policy-making. Thus, we have a case for interest-rate smoothing.
URN:NBN:fi:bof-20140807171
Keywords: E52; F31; 330; determinacy; E-stability; foreign exchange; inertia; Taylor rule